2017
DOI: 10.1101/183285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ldb1 and Rnf12-dependent regulation of Lhx2 controls the relative balance between neurogenesis and gliogenesis in retina

Abstract: Precise control of the relative ratio of retinal neurons and glia generated during development is essential for visual function. We show that Lhx2, which encodes a LIM-homeodomain transcription factor essential for specification and differentiation of retinal Müller glia, also plays a critical role in the development of retinal neurons. Overexpression of Lhx2, and its transcriptional coactivator Ldb1, triggers cell cycle exit and inhibits both Notch signaling and retinal gliogenesis.Lhx2/Ldb1 overexpression al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Multiple studies have documented Neurog2 expression in retinal progenitor cells (RPCs) between E11 to P2 (Akagi et al, 2004; Brown et al, 1998; Brzezinski et al, 2011; de Melo et al, 2018; Ma et al, 1996; Skowronska-Krawczyk et al, 2009), although there is conflicting data about when this gene shuts off between postnatal day 0 (P0) and P2. So, we labeled early postnatal retinal cryosections with a validated antibody and directly compared Neurog2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have documented Neurog2 expression in retinal progenitor cells (RPCs) between E11 to P2 (Akagi et al, 2004; Brown et al, 1998; Brzezinski et al, 2011; de Melo et al, 2018; Ma et al, 1996; Skowronska-Krawczyk et al, 2009), although there is conflicting data about when this gene shuts off between postnatal day 0 (P0) and P2. So, we labeled early postnatal retinal cryosections with a validated antibody and directly compared Neurog2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, immunostaining for P27 Kip1 and GLUL in Müller Glia is reduced both by overexpression 23 and downregulation of Lhx2 in the neonatal retina 9 , suggesting a balanced amount of LHX2 protein may be necessary to mediate the gliogenic process and a graded transcriptional response of target genes. Transcriptional de-regulation of P27 Kip1 and Glul may ultimately result from threshold responses that override the feed-forward regulatory loop controlling Lhx2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Mammals have a close homolog to LDB2, namely LDB1 (Matthews & Visvader, 2003; Love et al , 2014), and many studies have reported the role of LDB1 in multiple biological processes (Love et al , 2014; Costello et al , 2015; Ediger et al , 2017; de Melo et al , 2018; Kinare et al , 2019). In contrast, little is known about the biological functions of LDB2, especially in the brain, while the protein has been regarded as a layer V‐specific expression marker in the cerebral cortex (Bulchand et al , 2003; Molyneaux et al , 2007).…”
Section: Introductionmentioning
confidence: 99%